Premature deaths by visceral leishmaniasis in Brazil investigated through a cohort study: A challenging opportunity? - Ana Nilce S Maia-Elkhoury; Gustavo Adolfo Sierra Romero; Samantha Y O B Valadas; Marcia L Sousa-Gomes; José Angelo Lauletta Lindoso; Elisa Cupolillo; Jose Antonio Ruiz-Postigo; Daniel Argaw; Manuel J Sanchez-Vazquez (Public Library of Science (PLoS), 2019)
Background Visceral Leishmaniasis (VL) is the most severe form of leishmaniasis because it can lead to death. In the Americas, 96% of cases are in Brazil, and despite efforts, the fatality rate has increased in the past years. We analyzed deaths associated to VL in Brazil and investigated the factors that could influence on the timeliness of fatal outcome with emphasis on time (tStoD). Methodology The registered deaths by VL were sourced from the Brazilian National Notification System from 2007-2014. Through a retrospective cohort study, univariate and multivariable Cox proportional hazards model analysis were performed and investigated the factors that could influence the time (tStoD). These factors were analyzed through survival models. Results Out of the 1,589 reported deaths, the median for onset of the symptoms and the case notification date (tStoN) is 25 days (10-61), and for date of case notification and death (tNotD) is 9 days (4-17). The time (tStoN) to event investigation for HIV non-infected individuals was 1.4 (1.16-1.68) greater than the HIV positive group. At the same time peri-urban and urban area were 0.83 (0.47-1.44) and 1.33 (1.16-1.52), respectively. The explorations revealed apparent differences between the time to event investigation (both for tStoN and tNotD) and the age at the onset of the symptoms. According to the tStoN the rate of notification is 1.73 times greater in patients under 5 years old at the onset of the clinical symptoms compared to older patients. Conclusion VL patients under 5 years old were diagnosed earlier and had shorter survival. It could mean that in younger population, although properly diagnosed, the fatality pattern might be related to the severity of the disease. Main host characteristics were evaluated, and age and co-infections seem to have an impact in the disease progression.